Pandemi Covid-19 dalam Kacamata Islam - Titin Nurhidayati; M. Nafiur Rofiq (FALASIFA : Jurnal Studi Keislaman, 2021)
At the end of 2019 almost all countries were affected by thevirus outbreak Covid-19which caused a fairly high death rate. Coronaviruses (CoV) cause flu to more serious illnesses such as (MERS-CoV) and (SARS-CoV). The outbreak of this virus has caused paralysis of vital sectors such as economic, social, political, cultural and even religious. This pandemic condition makes everyone adapt to new habits. Therefore, the termappears new normal or a new life orderwhich is often heard due to this pandemic. This pandemic requires the state to issue rules and policies. With the outbreak of the covid-19 virus, we as believers do not need to worry about dealing with it, but we must remain vigilant. Always ask for protection from God, pray, strive to do what is recommended to prevent the transmission of the covid-19 virus outbreak, by always maintaining cleanliness and always washing hands, Large-Scale Social Restrictions, rest assured that the healing that will be given God, always be patient and grateful, and trust in God and always believe in the healing that will be given by God Pada akhir tahun 2019 terjadi hampir di seluruh negara terkena wabah virus covid-19 yang menyebabkan angka kematian yang cukup tinggi. Coronaviruses (CoV) menyebabkan timbulnya penyakit flu sampai yang lebih serius seperti (MERS-CoV) dan (SARS-CoV). Mewabahnya virus ini menyebabkan kelumpuhan sektor vital seperti ekonomi, sosial, politik, budaya dan bahkan agama. Kondisi pandemi ini membuat setiap orang untuk beradaptasi kebiasaan baru. Karenanya muncul istilah new normal atau tatanan kehidupan baru yang sering sekali terdengar akibat pandemi ini. pandemi ini mengharuskan negara menerbitkan aturan dan kebijakan. Dengan adanya wabah virus covid-19 ini kita sebagai seorang mukmin tidak perlu khawatir dalam menghadapinya, tetapi kita harus tetap waspada. Selalu meminta perlindungan kepada Allah Swt, berdoa, berikhtiar dengan melakukan hal yang dianjurkan untuk pencegahan penularan wabah virus covid-19 tersebut, dengan selalu menjaga kebersihan dan selalu mencuci tangan, Pembatasan Sosial Berskala Besar, yakinlah kesembuhan yang akan diberikan Allah SWT, selalu bersabar dan bersyukur, serta tawakal kepada Allah Swt dan selalu yakin akan kesembuhan yang akan diberikan oleh Allah SWT.